Efficient detoxication of hydroxylamine and nitrite through heterotrophic nitrification and aerobic denitrification by Acinetobacter johnsonii EN-J1 - Zhang, Manman; He, Tengxia; Wu, Qifeng; Chen, Mengping (Frontiers in Microbiology, 2023)
The roles of hydroxylamine (NH2OH) and nitrite (NO2–N) in accelerating the elimination of multiple nitrogen sources by a novel isolated strain of Acinetobacter johnsonii EN-J1 were investigated in this study. The results demonstrated that strain EN-J1 could eliminate 100.00% of NH2OH (22.73 mg/L) and 90.09% of NO2–N (55.32 mg/L), with maximum consumption rates of 1.22 and 6.75 mg/L/h, respectively. Prominently, the toxic substances NH2OH and NO2–N could both facilitate nitrogen removal rates. Compared with the control treatment, the elimination rates of nitrate (NO3–N) and NO2–N were enhanced by 3.44 and 2.36 mg/L/h after supplementation with 10.00 mg/L NH2OH, and those of ammonium (NH4+-N) and NO3–N were improved by 0.65 and 1.00 mg/L/h after the addition of 50.00 mg/L NO2–N. Furthermore, the nitrogen balance results indicated that over 55.00% of the initial total nitrogen was transformed into gaseous nitrogen by heterotrophic nitrification and aerobic denitrification (HN-AD). Ammonia monooxygenase (AMO), hydroxylamine oxidoreductase (HAO), nitrate reductase (NR) and nitrite reductase (NIR), which are essential for HN-AD, were detected at levels of 0.54, 0.15, 0.14 and 0.01 U/mg protein, respectively. All findings confirmed that strain EN-J1 could efficiently execute HN-AD, detoxify NH2OH and NO2–N, and ultimately promote nitrogen removal rates.